The effect of administrative diversity on job satisfaction: A comparative study of the opinions of a sample of workers in the telecommunications companies Asia and Zain Iraq - Al‐Salim, Ahmed Abdulsalam Ahmed; shubakie, Eshaq Yousif Hamdan Firas Imad Ali al (The journal of contemporary issues in business and government, 2021)
The human element is the determinant of the administrative process to achieve the goals of individuals and the organization, and the language of diversity has become one of the features of small and large contemporary organizations, local and international, as it gives them the ability to achieve sustainable competitive advantages, which made it necessary to understand the linkage and integration of human resources and their treatment without any discrimination or exclusion and under any reason. To come out with characteristics and ideas that contribute to achieving job satisfaction, which is considered one of the important topics covered by research and studies in the field of managerial psychology, because individuals spend most of their time at work and their satisfaction with it leads to increased production and profits and thus the success, effectiveness, survival and sustainability of management.